Jack and the beanstalk: read me story play( big book) - French, Vivian; Horse, Harry (Walker London, 2001)
"Walker Story Plays" are dramatic versions of popular nursery stories that children will already be familiar with. The plays are written for four voices, with the parts clearly denoted by different colour bands